Sandwich-type architecture film based on WS2 and ultrafast self-expanded and reduced graphene oxide in a Li-ion battery - Wenelska, Karolina; Kędzierski, Tomasz; Bęben, Damian; Mijowska, Ewa (Frontiers in Chemistry, 2023)
Since its discovery, graphene has been widely considered a great material that has advanced the Li-ion battery field and allowed development in its performance. However, most current graphene-related research is focused on graphene-based composites as electrode materials, highlighting the role of graphene in composite materials. Herein, we focused on a three-dimensional composite film with unique sandwich-type architecture based on ultrafast self-expanded and reduced graphene oxide (userGO) and exfoliated WS2. This strategy allows non-active agents [e.g., carbon black and poly (vinylidene fluoride)] free electrodes in LIBs in the form of a film. The ultra-quick exothermal nature of the USER reaction allows the rapid release of internally generated gases to create highly porous channels inside the film. Hence, the improved Li-ion transport in the LIBs boosted the electrochemical performance of both film components (ex-WS2 and reduced graphene), resulting in a high specific capacity of 762 mAh/g at .05 A/g and high Coulombic efficiency (101%) after 1,000 cycles. Overall, userGO showed the highest capacity at a low current, and ex-WS2 provided a higher reversible capacity. These results showed that the expanded graphene layer is an excellent shield for ex-WS2 to protect against pulverization, promoting both stability and capacity.